2021
DOI: 10.3390/nu13113679
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Rank Regression-Derived Dietary Patterns Related to the Fatty Liver Index and Associations with Type 2 Diabetes Mellitus among Ghanaian Populations under Transition: The RODAM Study

Abstract: The Fatty Liver Index (FLI) is a proxy for the steatotic component of non-alcoholic fatty liver disease (NAFLD). For sub-Saharan African populations, the contribution of dietary factors to the development of NAFLD in the etiology of type 2 diabetes mellitus (T2DM) remains to be clarified. We identified sex-specific dietary patterns (DPs) related to the FLI using reduced ranked regression (RRR) and evaluated the associations of these DPs with T2DM. This analysis used data from the RODAM, a multi-center cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…NP1 explained 9.5% of the variation in genetically adjusted PC1 and 0.01% of the variation of genetically adjusted PC2, so this nutrient pattern may be measuring a diet that promotes a state of resiliency to stress. This is a similar percent explained in other RRRs with biomarkers as response variables [ 89 , 90 , 91 ] and similar factor loadings to other RRR-derived dietary patterns [ 92 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 73%
“…NP1 explained 9.5% of the variation in genetically adjusted PC1 and 0.01% of the variation of genetically adjusted PC2, so this nutrient pattern may be measuring a diet that promotes a state of resiliency to stress. This is a similar percent explained in other RRRs with biomarkers as response variables [ 89 , 90 , 91 ] and similar factor loadings to other RRR-derived dietary patterns [ 92 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 73%
“…23 24 The RODAM study has identified various cross-sectional factors associated with CVD risk factors. [25][26][27] In addition, the study has resulted in the first EWAS for type 2 diabetes in SSA, in which we identified several CpG sites that were differentially methylated between type 2 diabetes cases and controls at an epigenome-wide level. 28 In our study of epigenome-wide DNA methylation differences between migrant and non-migrant Ghanaians, we identified 13 differentially methylated positions and 3 differentially methylated regions between migrants and non-migrants, with DNA methylation differences ranging from 0.1 to 4.5%.…”
Section: Findings To Datementioning
confidence: 99%
“…Food environments include physical, economic, policy, and socio-cultural surroundings, opportunities, and conditions that influence people's food consumption patterns, and acknowledge them as determinants of health (12) . Migration to a HIC is also accompanied by changes in the physical environment and the adoption of dietary behaviour of the host country (13,14) , which have been associated with the risk of Cardiovascular Diseases (CVDs), obesity and T2D (8,15) . As a response to this rising burden of NR-NCDs, the World Health Organisation (WHO) recommends preventive strategies that target underlying modifiable behaviours like dietary behaviours and social determinants through the creation of healthier food environments (16) .…”
mentioning
confidence: 99%